A Comparative Review of Human Rights Approaches in Programming National Action Plan for Protection of Human Rights of Persons with Albinism in Malawi - Msipa, Dianah (University of Pretoria, 2023)
Min Dissertation (MPHil (Disability Rights in Africa))--University of Pretoria, 2022.